THE ROLE OF WOMEN IN THE SUMATRAN WORKFORCE - Silaban, Angelica Laurina; Elasa, Dea Tia; Wantoya, Qiara; Pratiwi, Yulia Citra; Meisuri, Meisuri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
This article investigates the position of women in the workforce in Sumatra, concentrating on the ongoing gender disparities caused by conventional cultural norms and structural bias. Despite growing awareness of gender equality, women in Sumatra, particularly within patriarchal Batak communities, face major impediments to leadership opportunities, fair recruitment processes, wage parity, and professional advancement. Changes in society are increasingly promoting women's participation in male-dominated industries, yet challenges persist. The report emphasizes the importance of policy reforms such as equal education, gender-sensitive employment practices, and positive cultural developments. These policies seek to create a more inclusive workplace, improve women's socioeconomic status, and promote regional growth.